Role of Islamic Religious Union (Persis) Bandung in Implementation of Islamic Education - Achjadilaga, Undang; Yusoff, Abdullah (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2019)
Islamic Association (PERSIS) Bandung play role in Islamic education. Although many studies in term Islam education have been done by previous scholars, but studies on the role PERSIS in implementation of Islamic Education is still very much lacking. Therefore, the objective of this paper is to study the role Persis in implementation of Islamic education in Jawa Barat (West Java) Indonesia. And to discuss any characteristics of Islamic Education. The case study selected for this paper is Jawa Barat (West Java). This is a qualitative study using data from documents as a primary source. The method of thematic analysis was used to analyzed the data collected. Through this method, the themes of the role of Persatuan Islam (Persis) in implementation of Islamic education in West Java was discussed. The conclusion from this current study found that Islamic education in Persatuan Islam (Persis) had played three critical aspects role in implementation of Islamic Education. Three of it are related to three levels of education. (1) basic Islamic education, (2) middle Islamic Education and (3) middle–up Islamic education. Islamic Education in Persis mix any characteristics as well as classical pesantren or modern in system of administration.